Empirical analysis on the effect of gross vehicle weight and vehicle size on speed in car following situation - Abdullah, A.; Karem, M.R.; Yamanaka, H.; Okushima, M. (2011)
This study attempts to explore empirically how gross vehicle weight (GVW) of following vehicle and size of leading vehicle will affect the driver behavior in controlling their speed under different compositions of leader-follower pairs in a car-following situation. A large sample of traffic and vehicular data for various vehicle types were obtained continuously using a weigh-in-motion (WIM) based transport data collection system installed at Federal Route 54 in Malaysia. Then, statistical analysis was applied to explore the driver behavior in controlling the speed in a car-following situation from two different perspective: driver’s visual input and vehicle dynamics capability. The main findings of this study are when we incorporate the vehicle dynamic’s capability in a car-following situation, the GVW of following vehicle and the size of leading vehicle were significant sources of variation in following vehicle speed and relative speed, and their interaction influence the driver behavior in controlling the speed.